Characteristics of top coal fall in front of face support in longwall: A case study - Le, Tien Dung; Vu, Dinh Hieu; Nguyen, Anh Tuan (Vietnam Journal of Earth Sciences, 2020)
Top coal fall in front of face support severely affects the safety and productivity in mechanized longwall mining. This paper presents a discontinuous numerical analysis on the important characteristics of the fall such as abutment stress, material failure, and fall mode. A top coal fall model is validated against site observation and past numerical and empirical studies. The numerical results provide further evidence confirming that horizontal stress relaxation, vertical stress concentration, and strength and structure of coal seam control the failure of top coal ahead of support. Top coal fall in longwall mining with large caving height is found in “stress caving” mode or, in other words, “horizontal stress-driven guttering” mechanism. A pre-existing fault running into a mined-out area can facilitate the occurrence of face spall but may not lead to top coal fall.  The results of this study are particularly helpful to engineers in developing proper remedy or prevention solutions to top coal/roof fall incidents.